Downregulation of WNT8A, LRP5, LRP6 and FGF8 in Malay non-syndromic cleft lip and/or palate patients - Nurul Syazana Mohamad Shah,; Wan Azman Wan Sulaiman,; Sarina Sulong,; Ahmad Sukari Halim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Non-syndromic cleft lip and/or palate (NSCL/P) is a one of the most common birth defects occurs as a result of multi-factorial determinants such as genetic and environmental factors. Genetic factor has been studying widely across different population in identifying genes causing cleft defects. This study aims to validate the role of fibroblast growth factors (FGFs) and signalling molecules Wingless-type (Wnt) to the occurrence of cleft lip and/or palate among Malay population. Tissue skin was obtained from consented NSCL/P patients who underwent the cleft lip repair operation at the upper lip skin area and non NSCL/P individual was obtained from patient having traumatic injury at the lip area as a control. Expression pattern of FGF8, FGF10, Wnt8a, and LRP5/6 were tested and validated using Western Blot (WB) and quantitative Reverse Transcriptase-PCR (qRT-PCR). The fold change difference of FGF8 (0.614 ± 0.1012-fold), FGF10 (0.7188 ± 0.1017-fold) and Wnt8a protein (0.9051 ± 0.0142-fold) was downregulated by 1-fold in cleft lip (CL) tissues compared to the normal meanwhile LRP5/6 protein (1.2201 ± 0.1404-fold) was found upregulated by 1-fold. Validation testing confirmed that expression of FGF8 (p=0.014), Wnt8a (0.0762 ± 0.0227), LRP5 (0.3577 ± 0.1362) and LRP6 (0.3093 ± 0.2541) were significantly reduced in CL tissues compared to normal. This is the first study identified defective regulation of Wnt8a, LRP5, LRP6 and FGF8 in NSCL/P among Malays. These novel findings clearly explained the important role of growth factors FGF and Wnt signalling pathway in lip and palate formation during craniofacial development.